Polysaccharide and protein-based functional wound dressing materials and applications. Issue 2 (22nd January 2022) - Debele, Tilahun Ayane; Su, Wen-Pin
Abstract: In chronic wounds area, there is an abnormally low amount of extracellular matrix, which urges for the extra new biomimetic material to promote proper wound healing. Because of their unique characteristics such as inherent bioactivity, biocompatibility, biodegradability and mimicking the natural ECM, natural polymer and their derivative are widely explored as the functional active wound dressing and carrier of antimicrobial agents or growth factors to enhance wound healing. In this review, the wound healing application of polysaccharides, proteins and their derivatives as the active wound dressing and as the carriers of pharmaceutical agents was briefly reviewed. Graphical Abstract: UF0001